Organising R&D in globalised context: Convergence or divergence? The relative influence of Dutch and foreign cultures on the organisational structure of R&D in multinational corporations - Anneke Offereins; Ben Fruytier (Management Revue, 2006)
This paper examines national culture as an explanatory variable in the convergence versus divergence debate of R&D organisational structures. It explores the effects of globalisation on the way in which R&D processes are structured at group level. It is argued that culture may have a decisive effect on R&D group-structure. On the one hand the results of the study observe a converging trend towards a universal organisational structure under influence of a predominantlyAnglo-Saxon-based culture. On the other hand, there is a persistence of differences owing to the dominance of the domestic culture on the one side and the increasing multicultural composition of the R&D staff at the laboratories on the other side, which points to divergence. The research was conducted at eight of the ten most innovative MNCs in the Netherlands. It builds on scientific studies regarding organisational design in R&D (Chiesa 1996, 2001; Donaldson 2001; De Sitter 1998; Tidd et al. 2001) and includes the conceptual frameworks by Hofstede for analysing cultural diversity, complemented by contributions to the convergence-divergence debate (Ferner 1997; Harzing/Sorge 2003).
Keywords: 650; national culture; research & development; organisational structure; Nationalkultur; Betriebliche Forschung; Organisationsstruktur; Multinationales Unternehmen; Niederlande